276 UTEROPLACENTAL INSUFFICIENCY ALTERS KIDNEY CYCLOOXYGENASE 2 EXPRESSION AND CAUSES ADULT-ONSET HYPERTENSION. (1st January 2006) - Baserga, M.; Hale, M. A.; Clarke, B. R.; McKnight, R. A.; Calloway, C.; Lane, R. H.
Abstract : Background: IUGR predisposes the fetus towards increased corticosterone levels, decreased nephron number, and adult-onset hypertension. Rats rendered IUGR by uteroplacental insufficiency (UPI) also have increased corticosterone levels and suffer reduced nephron number. A possible mechanism through which steroids decrease nephron number is regulation of the inducible enzyme cyclooxygenase 2 (COX-2), a pivotal protein in nephrogenesis; however, the effect of UPI upon COX-2 expression is unknown. Furthermore, the association of reduced nephron number and adult-onset hypertension has not been assessed in our animal model. Hypothesis: We hypothesized that IUGR and subsequent glucocorticoid overexposure of the fetus lead to decreased kidney COX-2 expression and protein levels at birth and predispose towards adult-onset hypertension. Methods: Bilateral uterine artery ligation was performed on day e19 pregnant Sprague-Dawley rats and pups were harvested at term (e21.5). Levels of COX-2 mRNA, and protein were quantified using real-time RT-PCR and Western blotting from whole kidneys on d0 and d21 of life (juvenile rat). Systolic (SBP), diastolic (DBP), and mean blood pressure (MBP) were measured on d21 and d120 of life by tail cuff method. Results: On d0, IUGR was associated with decreased kidney COX-2 mRNA levels (79 ± 7* % of control) and protein levels (69 ± 3%** of control). Kidney COX-2 mRNA and protein levels were unaffected in d21 IUGR juvenile rats. Though blood pressure was not significantly different on d21 of life among groups, SBP was significantly higher in both males and females IUGR adults on d120 of life when compared to control animals (176 ± 7 vs 159 ± 4*** and 149 ± 9 vs 128 ± 7**, respectively). MBP and DBP were also significantly higher in IUGR female rats but not affected in IUGR males on d120 (* p < .05, **p < .01, ***p < .001). Conclusions: In vitro studies demonstrate that steroid exposure decreases COX-2 expression in renal cells. In vivo studies demonstrate that COX-2 inhibition impairs nephrogenesis. In our animal model, UPI decreases fetal COX-2 expression during a period of active nephrogenesis in the IUGR rat, which is also characterized by decreased nephron number and adult-onset hypertension. We speculate that decreased IUGR kidney COX-2 levels reduce nephron number and lead to adult-onset hypertension. Supported by the University of Utah Department of Pediatrics CHRC.